Non-linear analysis of nitrogen pressure drop instability in micro/mini-channels. (February 2020) - Kuang, Yiwu; Wang, Wen; Miao, Jianyin; Zhang, Hongxing; Yu, Xin'gang
Highlights: Analysis of nitrogen pressure drop instability in micro/mini-channels is conducted. A novel stability criterion consists of 4 dimensionless numbers is presented. A stability map considering acceleration pressure drop effects is proposed. Influences of channel dimensions on the instability are studied. Abstract: Pressure drop instability of nitrogen flow boiling in micro/mini-channels challenges the application of nitrogen in the cooling & heat dissipation areas by causing unstable flows, oscillations of flow rate, temperature and pressure. In the present study, a non-linear analysis of nitrogen flow boiling instability is conducted. By introducing the structure number, a novel stability criterion consisting of 4 dimensionless numbers are proposed. Based on the criterion a stabilization map is obtained and validated with experimental data from different researchers. Influences of acceleration pressure drop, saturation pressure, channel length, diameter and length-diameter ratio on the stabilization map are investigated. It is found that acceleration pressure drop plays a significant role in the nitrogen flow boiling instability and has opposite effects to the frictional pressure drop. Increasing of saturation pressure generally stabilizes the nitrogen boiling flow by compressing the unstable region on the stabilization map. Besides, these is a maximum allowable subcooling number which ensures the flow boiling system to be inherently stabile if it is not exceeded. And it increases with the growth of saturation pressure. Furthermore, channels with the same length-diameter ratio have very similar stabilization map. Length-diameter ratio can be a significant parameter for further similarity analysis of nitrogen flow boiling instability.